Reviewing Batik with Natural Coloring based on the Clean Production Theory with an Ecofeminist Perspective (Case Study: Putri Kawung Batik Community in Klaten) - Levi, Purwanti Asih; Hunga, Arianti Ina Restiani; Sidabalok, Hotmauli (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2021)
Mass and rapid production of batik using synthetic color and printing techniques engenders environmental problems such as waste production, air pollution, water pollution, unhealthy and hazardous work environment, and a threat to the sustainability of hand-drawn batik. Clean production is one solution to this problem. This paper discusses the practice of batik with natural coloring based on the theory of clean production with an ecofeminist perspective. The method employed in this research is a case study with a one-unit production (cluster) approach of Putri Kawung batik community. The findings show that the practice of clean batik production in Putri Kawung batik community still focuses on the input and process of using natural coloring, material selection, and reuse of wax materials. This shows that the role of women through community gradually practices clean production, even though it has not yet extended to its output processing.